Review of Relevant Literature About Critical Thinking Skills in a Science Perspective - Ana Silfiani Rahmawati; Ida Hamidah; Achmad Samsudin; Diana Rochintaniawati (Postgraduate, University of Mataram, 2025)
Critical Thinking (CR) is one of the most important thinking skills and is a widely recognized measure of the quality of student learning. The literature reviewed shows the importance of integrating critical thinking (CR) into curriculum content and teaching methods in a tiered manner. This study uses the Systematic Literature Review (SLR) method, to map where CT is taught, which countries have research trends on CT, how to teach and assess CT, and the influence of technology on CT. Documents were analyzed comprehensively in the Scopus database for the 2018-2023 period. There are five stages of SLR research, namely determining keywords, searching for data, selecting documents, validating data, and analyzing data. Only documents in the form of articles published in the journals used were analyzed. The results of the study indicate that critical thinking skills must be taught and trained at the school level, both in elementary schools, secondary schools, and in certain courses. CT teaching is carried out by choosing the right model or strategy, for example using a modified inquiry model or STEM approach strategy. Assessment is carried out using instruments such as critical thinking skills tests or observation rubrics that have been standardized or modified to obtain accurate results.